The Economic Impacts on Germany of a Potential Russian Gas Shutoff - Lan, Ting.; Sher, Galen; Zhou, Jing. (Washington, D.C. : International Monetary Fund, 2022)
We analyze the potential impacts on the German economy of a complete and permanent shutoff of the remaining Russian natural gas supplies to Europe, accounting for the curtailment of flows through Nord Stream 1 that has already taken place. We find that such a scenario could lead to gas shortages of 9 percent of national consumption in the second half of 2022, 10 percent in 2023 and 4 percent in 2024, which would be worse in the winter months, and would likely fall on firms, given legal protections on households. We combine the effects of less gas on production with the consequent effects of reduced supply of intermediate goods and services to downstream firms, and with reduced economic activity due to rising uncertainty. Together, these three channels reduce German GDP relative to baseline levels by about 1.5 percent in 2022, 2.7 percent in 2023 and 0.4 percent in 2024, with no gains in subsequent years from deferred economic activity. The associated rise in wholesale gas prices could increase inflation by about 2 percentage points on average in 2022 and 2023. Our simulations suggest that the economic impacts can be reduced significantly by having households voluntarily share a small part of the burden, and by rationing gas supplies more to more gas-intensive and downstream firms. We also suggest other ways to enhance German energy security.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Conflicts; Macroeconomics; Negotiations; Sanctions